Analyzing the Moderating Role of Corporate Reputation in the Relationship between Managerial Ownership and Voluntary Disclosure in Leveraged and Capital-Based Firms - Bahreyni, Vahid; Dastgir, Mohsen; Moradi, Mohammad Ali (Business, Marketing, and Finance Open, 2026)
The purpose of this study is to analyze the moderating role of corporate reputation in the relationship between managerial ownership and voluntary disclosure in leveraged and capital-based firms. This research can be useful for investors in selecting appropriate investment portfolios and can also assist stock market policymakers in enforcing disclosure quality requirements and promoting greater stability in the capital market. To estimate the research model and test the hypotheses, a panel data econometric approach was employed. Firm-level data were extracted from the Rahavard Novin database and the website of the Tehran Stock Exchange Organization, and the hypotheses were tested using EViews software. The statistical population consisted of companies listed on the Tehran Stock Exchange from the beginning of 2012 to the end of 2021, covering a ten-year period, during which the firms continuously maintained their listing status. After applying sample selection criteria, 141 firms met the requirements and were selected as the final sample. The results indicate that corporate reputation weakens the relationship between managerial ownership and the level of voluntary disclosure in leveraged firms, while it strengthens this relationship in capital-based firms. Capital-based firms with higher corporate reputation are more likely to disclose earnings forecasts than leveraged firms. Capital-based firms with stronger reputations are encouraged to preserve their reputation, which can be regarded as an intangible asset. In leveraged firms that lack strong reputational assets, building a high level of corporate reputation is more challenging, and such firms may therefore be less inclined to invest in reputation building.